A Rare Hepatocellular Carcinoma Metastasis to the Esophagus: A Case Report and Literature Review. (21st September 2018) - Lobo, Monica; Xiong, Zhenggang; Collins, Victoria
Abstract: Liver cancer is the second most common cause of death from cancer worldwide, with extrahepatic metastasis occurring in 30% to 75% of patients. However, gastrointestinal metastasis is not common and it is even rarer to have involvement of the esophagus. We report an unusual metastasis of hepatocellular carcinoma to the esophagus presenting as a gastroesophageal junction lesion in an 81-year-old man. The patient presented with abdominal pain, nausea, vomiting, gastrointestinal bleed, and low hemoglobin levels. Testing revealed elevated liver function enzymes, elevated AFP, and chronic hepatitis C infection. Ultrasound from an outside facility showed multiple liver masses and a computed tomography (CT) of the liver with multiphase contrast showed indistinct heterogeneous observations with patchy enhancements in segments 7 and 8 of the liver, measuring 10.2 × 6.3 cm, concerning for hepatocellular carcinoma. There was also enhancement at the gastroesophageal junction. In light of the CT findings, and in efforts to locate the patient's source of gastrointestinal bleeding, an esophagogastroduodenoscopy was performed and revealed a 2.3-cm mass located approximately 2.5 cm above the gastroesophageal junction. Biopsy showed atypical cells in pseudoglandular formation with nuclear pleomorphism and nuclear hyperchromasia, as well numerous mitoses. Immunostains were positive for Hep Par 1, glypican 3, and scattered AFP. The stains were negative for cytokeratin 5/6 and p63. There was a Ki-67 index of approximately 50%. This immunoprofile is consistent with a hepatocellular carcinoma. Although biopsy of the liver was not done, in consideration of the imaging, history of chronic hepatitis C infection, and immunoprofile, the diagnosis of metastatic hepatocellular carcinoma was made. This case shows that, although not common, liver carcinoma can metastasize to unlikely areas, such as the esophagus, and immunostains are essential in the differentiation a primary tumor from metastasis.